Effects of Articular Disc Position on Condylar Displacement in Unilateral Clenching - Shigeta, Yuhko; Ogawa, Takumi (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Purpose: The purpose of this study was to examine displacement of the condyle in unilateral clenching, and to clarify effects of disc position on the non-clenching side on temporomandibular joint loading. Methods: The subjects were 20 patients diagnosed with TMD who had previously agreed to be examined. They were asked to clench a plastic stick unilaterally between the upper and lower second molars. The resulting mandibular movements were then measured with a six-degree-of-freedom jaw-tracking device, and analyzed with a computer, using software designed specifically for this purpose. The subjects were divided into 2 groups according to the disc position on the non-clenching side: the NDD group (no disc displacement) and the DD group (disc displacement). The 2 groups were compared with each other. We also investigated the relationship between condylar displacement and evoked pain in the TMJ of the non-clenching side. Results: In the NDD group, the position of the condyle on the non-clenching side distributed around a point located slightly above the starting position. In the DD group, it distributed around a point located slightly antero-superior to the starting position. In the NDD group, the condyle on the non-clenching side was displaced further upward than the condyle on the clenching side in the majority of cases; in the DD group, this occurred in a smaller number of cases. In most patients who complained of evoked pain on the non-clenching side, the condyle on the non-clenching side displaced further upward than the condyle on the clenching side. In other words, differences in disc position seemed to correlate with condylar displacement. Conclusion: We conclude that differences in disc position affect condylar displacement in unilateral clenching, and this suggests that disc position also affects temporomandibular joint loading.